“Auditoría financiera a la cooperativa de ahorro y crédito Cámara de Comercio La Maná, período 2018”. - Macias Valdez, Karla Lilibeth (2020)
Maintaining the reliability of the financial statements is a great support for financial institutions, taking into account the previous premise, it was considered essential to carry out a financial audit of the Savings and Credit Cooperative “Chamber of Commerce La Maná” of the canton La Maná, province of Cotopaxi, for the period from January 1 to December 31, 2018, using qualitative research, with the Manager and the 6 employees of the cooperative as a population. Through the evaluation of the internal control, it was established that the level of compliance with the plans and program of the financial management of the Savings and Credit Cooperative "Chamber of Commerce La Maná" is not adequate because employees are unaware of the functions within his position based on manuals or established policies. Once the horizontal analysis applied to the balance sheet for the 2017-2018 year was carried out, it was known that the account of available funds showed a growth of 12% based on the year 2017; also, the credit portfolio had an increasing trend being that in 2017 had $ 284,456.01 and for the year 2018 it was $ 318,449.59. In the liabilities accounts it was evidenced that the obligations with the public did not have greater growth with 0.26%. While the calculation of financial ratios showed that revenues increased by 33% in relation to the previous year, the debt ratio reflected that there was a decrease of 2%. Suggested recommendations include implementing a policy manual for cash management, a device that allows the detection of counterfeit bills, permanent training for the staff of the Cashier Area, implementing policies on password protection, establishing policies Clear for accounts receivable in the existing credit manual, designate a person responsible for monitoring and inspecting the titles and bonds, complying with the deadlines and formats established for this purpose.